Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae) - Przewoźny, Marek; Greń, Czesław; Jäch, Manfred A. (Zootaxa, 2016)
Limnebius (s.str.) agnieszkae sp. n. from the Crimean Peninsula (Ukraine) is described. It is a member of the Limnebius furcatus subgroup of the L. parvulus species group. The new species is very similar to L. stagnalis Guillebeau, 1890, from which it can be distinguished by the aedeagus only. Information about its habitat and a list of other water beetles found together with the new species are provided. Limnebius myrmidon Rey, 1883 is recorded for the first time from the Ukraine.